Analysis of Systematic Studies in Research Mapping Entrepreneurs in the Metaverse Era - Dwi Putri, Uswatun Hasanah; Fitriyani, Chiandria; Setiawan, Adi (International Journal of Engineering, Science and Information Technology, 2025)
The Metaverse refers to a virtual environment concept that evolves in parallel with the real world, driven by technological advancements. In the present day, the Metaverse functions as a medium for entertainment and an emerging ecosystem where entrepreneurs can innovate and expand their businesses. This study aims to review existing literature on the Metaverse within the entrepreneurship framework and comprehensively analyze its role as a dynamic business platform for entrepreneurs. This research also seeks to map the studies conducted to help researchers and businesses explore and develop the potential of the Metaverse as a future entrepreneurial opportunity. The Metaverse provides opportunities for entrepreneurs to implement innovative promotional strategies in the digital world, which mimic real-world business dynamics. In the context of industry, the Metaverse is increasingly strengthening its position as a new entrepreneurial ecosystem, and some companies have started to utilize it for business expansion. The qualitative method used in this research is a bibliometric technique through the Visualization of Similarities (Vosviewer) application, with the keywords metaverse, entrepreneur, digital, and experience. This research identified 258 articles, which were then analyzed using Vosviewer. The results of this analysis produce a mapping of scientific developments related to the Metaverse and reveal potential future research that can be a reference for researchers in developing research in the entrepreneurship field in the metaverse era.